Digital Demand Signals for Global Halal Business Markets: A Search Analytics–Based Opportunity Index - Asep Koswara; Rijalul Khaer; Nila Nopianti (Jurnal Ekonomi Islam, 2025)
Digital search behavior has emerged as a valuable source of market intelligence capable of capturing consumer interest before it is reflected in conventional economic indicators. However, existing studies on the halal industry remain fragmented, predominantly focusing on individual sectors without providing a comprehensive framework for evaluating global market opportunities. This study develops the Global Halal Industry Opportunity Index (GHIOI) by integrating search engine analytics and machine learning to assess digital halal market opportunities across 250 countries and territories. Weekly Google Trends data from 2019–2025 covering Halal Food, Halal Cosmetics, Halal Tourism, and Islamic Finance were transformed into a multidimensional composite index and analyzed using K-Means clustering. The findings reveal considerable cross-country heterogeneity, with Brunei, Maldives, Singapore, and Malaysia exhibiting the strongest digital opportunity profiles. The clustering results further distinguish countries into high-, emerging-, and developing-opportunity groups, providing a more nuanced understanding of global halal market dynamics. By converting digital search signals into a composite measurement framework, GHIOI offers a leading indicator that complements conventional economic statistics. The proposed framework advances digital business and Islamic economics research while providing evidence-based market intelligence for policymakers, investors, exporters, and halal industry practitioners.